Prospective Multicenter Assessment of Intraoperative and Perioperative Complication Rates Associated with Adult Spinal Deformity (ASD) Surgery in 558 Patients. Issue 1 (April 2016) - Klineberg, Eric; Smith, Justin; Lafage, Virginie; Shaffrey, Christopher; Bess, R. Shay; Schwab, Frank; Gupta, Munish Chandra; Hart, Robert; Protopsaltis, Themistocles; Mundis, Gregory; Kim, Han Jo; Burton, Douglas; et al.
Introduction: Few previous studies have focused on early (intraoperative and perioperative) complication rates for ASD surgery, with reported overall rates ranging from ~10% to 75%. However, most available studies are relatively small single- center series and likely underestimate complication rates due to retrospective design and lack of rigorous collection of complications. Accurately defining the early complication rates is particularly important for patient counseling with regard to the risks and benefits of surgical treatment. Material and Methods: As part of a prospective ASD database, standardized collection forms, on-site coordinators and auditing helped ensure complete capture of complications. Intraop and periop (<6 wks) complications were collected for all patients with these available data, regardless of subsequent length of available follow-up. Results: 558 patients underwent surgical treatment for ASD and had a mean age of 57 years, mean Charlson Comorbidity Index of 1.5 and previous surgery in 48%. The majority (98%) of patients had treatment including a posterior instrumented approach and included a 3-column osteotomy in 22% of patients. A total of 171 intraoperative complications (69 major, 102 minor) affected 127 (22.8%) patients, and a total of 272 perioperative complications (133 major, 139 minor) affected 185 (33.2%) patients. Collectively, 443 early complications (202 major, 241 minor) were reported, with 264 (47.3%) patients experiencing one or more complication. The overall mean numbers of intraoperative, perioperative and total complications per patient were 0.31, 0.49 and 0.79, respectively. Conclusion: ASD surgery is associated with high rates of early complications, with 47.3% of patients having at least one complication. These rates are substantially higher than previously reported. These finding may prove useful in treatment planning and patient counseling.